Biodecolorization of Methylene Blue by Using Bacillus subtilis Immobilized into SA-PVA-Bentonite Matrix in Mineral Salt Medium and Non-nutritious Medium - Alya Awinatul Rohmah; Adi Setyo Purnomo; Widiya Nur Safitri (Universitas Gadjah Mada, 2022)
Industrial dye wastewater can potentially cause significant harm to organisms and the environment across the world. Methylene blue (MB) is a synthetic dye that can be found in wastewater. Immobilizing clay material and degradative bacteria into a carrier is the best way to remove MB. Therefore, this study aimed to immobilize Bacillus subtilis in sodium alginate (SA)-polyvinyl alcohol (PVA)-Bentonite for adsorption and degrading MB in nutritious mineral salt medium (MSM) and non-nutritious media. The result showed that SA-PVA-Bentonite-non-living B. subtilis beads (SPB-nBS) had the highest result in non-nutritious medium, approximately 88.89%. While in nutritious MSM, living B. subtilis addition into beads (SPB-BS) reached the highest MB removal, which was 94.31%. Nutritious MSM had a role as the sole carbon and energy for living B. subtilis. So, it could adsorb and degrade MB by its enzymatic system. The degradation products were predicted as C7H10N2O4S, C8H10N2O2 and C6H8N2O3S. Hence, this study indicated that a nutritious medium was the suitable medium for MB degradation. According to the SEM result, the bacteria spread and covered the beads. Furthermore, the adsorption kinetics and isotherms were also analyzed; SPB beads followed the pseudo-second order kinetic model and Langmuir isotherm.